Nghiên cứu mối quan hệ giữa đổi mới, sáng tạo và khởi nghiệp đến tăng trưởng kinh tế - Phan Thị Bích, Nguyệt; Nguyễn Khắc Quốc, Bảo; Hồ Thị Thanh, Hằng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
The paper aims to answer the questions of whether innovation and entrepreneurship activities motivate economic growth, and if economic growth contributes to strong development of innovation and entrepreneurship activities. Through the sample of 30 countries including Vietnam in 2004-2014, the study investigates the relationships among innovation, entrepreneurship, and economic growth using fixed effects model (FEM) regression. In addition, the GMM technique is exploited to remove the existing constraints of FEM, thereby increasing the robustness of the results. The empirical findings show that entrepreneurial spirit and innovation are positively correlated with economic growth and that there also exist the reverse effects of economic growth on innovation and entrepreneurial spirit